The correlation of water with settlement and transportation network: a case study of Turkey - Atabeyoğlu, Ömer (Journal of Environmental Engineering and Landscape Management, 2016)
Cities, with their ancient history, are living formations that develop and change constantly. Although there are several economical, safety and transportation reasons for their foundation purposes and for the locations where cities founded, geographical conditions also significantly affect these reasons. One of the most important elements determining the area where the cities have been founded is the water. This article examined how the geographical water resources affect the humankind settlements and the transportation network. The relationships, similarities and differences between transport and water networks were revealed using fractal analysis method. The effect of water on the location of living areas was also determined by using the bufferzone method. Swot analysis was made for evaluated to affects of the roads on ecosystem and landscape. The study was carried out on the base of 81 provinces in Turkey. The roads in the country that was netted with dense transportation networks were passed through considering the geographic elements. Rivers, lakes and seas are important factors in determining the transit routes of the roads. The water elements use the routes for which geographic conditions are the most suitable and this serves as a guide for the transport network. Additionally, provincial and district centers have also been established to be particularly close to the water element due to its landscape and economic factors, the appropriate geographic and climatic conditions.